Persistence of Reduced Left Ventricular Function after Aortic Valve Surgery for Aortic Valve Regurgitation: Bicuspid versus Tricuspid - Petersen, Johannes; Neumann, Niklas; Naito, Shiho; Sequeira Gross, Tatiana; Massel, Robert; Reichenspurner, Hermann; Girdauskas, Evaldas (The Thoracic and Cardiovascular Surgeon, 2019)
Objective Long-term prognosis of patients with aortic regurgitation (AR) and reduced left ventricular ejection fraction (LVEF) who undergo aortic valve surgery (AVS) is unknown. Due to the congenital origin, bicuspid aortic valve (BAV) morphotype might be associated with a more severe cardiomyopathy. We aimed to evaluate the LVEF recovery after aortic valve replacement (AVR) surgery in patients with AR and reduced preoperative LVEF.Methods This retrospective analysis included 1,170 consecutive patients with moderate to severe AR who underwent AVS at our institution between January 2005 and April 2016. Preoperative echocardiography revealed 154 (13%) patients with predominant AR and baseline LVEF < 50%. A total of 60 (39%) patients had a BAV (BAV group), while the remaining 94 (61%) patients had a tricuspid morphotype (tricuspid aortic valve [TAV] group). Follow-up protocol included clinical interview using a structured questionnaire and echocardiographic follow-up.Results A total of 154 patients (mean age 63.5 ± 12.4 years, 71% male) underwent AVS for AR in the context of reduced LVEF (mean LVEF 42 ± 8%). Fifteen (10%) patients had a severely reduced preoperative LVEF ≤ 30%. Mean STS (Society of Thoracic Surgeons) score was 1.36 ± 1.09%. Mean follow-up was comparable between both the study groups (BAV: 50 ± 40 months vs. TAV: 40 ± 38 months, p = 0.140). A total of 25 (17%) patients died during follow-up. Follow-up echocardiography demonstrated similar rate of postoperatively reduced LVEF in both groups (i.e., 39% BAV patients vs. 43% TAV patients; p = 0.638). Cox's regression analysis showed no significant impact of BAV morphotype (i.e., as compared with TAV) on the postoperative LVEF recovery (odds ratio [OR]: 1.065; p = 0.859). Severe left ventricular (LV) dysfunction at baseline (i.e., LVEF ≤ 30%) was a strong predictor for persistence of reduced LVEF during follow-up (OR: 3.174; 95% confidence interval: 1.517–6.640; p = 0.002). Survival was significantly reduced in patients with persisting LV dysfunction versus those in whom LVEF recovered (log rank: p < 0.001).Conclusion Our study demonstrates that reduced LVEF persists postoperatively in 40 to 45% patients who present with relevant AR and reduced LVEF at baseline. Postoperative LVEF recovery is independent of aortic valve morphotype (i.e., BAV vs. TAV). Severe LV dysfunction (LVEF ≤ 30%) at baseline is a strong predictor for persistence of reduced LVEF in patients with AR and results in significantly reduced long-term survival.
Keywords: cardiac; cardiomyopathy; heart failure; heart valve; surgery